If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + 4) = 10 Reorder the terms: 5(4 + 2x) = 10 (4 * 5 + 2x * 5) = 10 (20 + 10x) = 10 Solving 20 + 10x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 10x = 10 + -20 Combine like terms: 20 + -20 = 0 0 + 10x = 10 + -20 10x = 10 + -20 Combine like terms: 10 + -20 = -10 10x = -10 Divide each side by '10'. x = -1 Simplifying x = -1
| b^3+4b^2+3b=0 | | .73x+.42(x-2)=35x | | 0.1-0.01(x+1)=-0.02(3-x) | | .18y+.07(y+8000)=2060 | | r^3=18-7r | | .73+.42(x-2)=35x | | 6(x-2)+4=3x+3(-1+x) | | 81x^3-24= | | x+(x+16)=1000 | | .73x+.42(x-2)=.35 | | 2x^2+12x+12=0 | | 19z-3(z-6)=66 | | 7x^2=3x+5 | | 9b^2-24bt+16t^2= | | 24f=156 | | 16.8=17.6t-0.8t^2 | | K+17=2 | | 5y+4(y-7)=4(y+2)-2 | | 169b^2-225= | | K+5=7 | | m+1-2=5-6 | | 12s^2-29sb+14b^2= | | 9+5s-6=9s+3-3s | | 19-4x=-6x+13 | | x^2-11x-8712=0 | | 3(5s+4)-5s=2(5s+2)-9 | | 3a-21a+6a-42= | | 6x+6=6(x+7) | | .1(x+40)+1.5x=68 | | 12(3x+3)-6(2x-6)=4x-68 | | (9x^2)(x)=9x^3 | | 8(n+7)=2(28+4n) |